THE IDENTITY OF LAI-RUE-FAI AT RASRI-SALAI, SISAKET PROVINCE - Butsabong, Niztha; Thantaree, Phanphilai; Lumfuay, Punnatut (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2022)
There are two objectives that belong to the identity of the Illuminated Boat Procession (Lai Ruea Fai) of RasiSalai District, Sisaket Province as follows: 1. To study the history of the Illuminated Boat Procession of RasiSalai District, Sisaket Province. 2. To study the events of the Illuminated Boat based on qualitative research. The study results found that the Illuminated Boat Procession was held by people in Sompoi subdistrict on the occasion of “Hitboon Khao Phansa (Buddhist Lent),” which was inherited as an intangible heritage. The ceremony is divided into three periods: the first period is in the morning, the second period is from midday to afternoon, and the third period is in the evening, at the end of Buddhist Lent. In each period, many behaviors represent the intellectual identity of the Sompoi subdistrict people, such as presenting black or red sticky rice to others, blowing the Snai(Buffalo horn), and the Ghosts eating flags, etc. Although some activities are made light or terminated with time, now, a group of the new young generation who are interested in, love, and cherish the intangible cultural heritage are trying to pull back and hold on to Sompoi subdistrict’s Illuminated Boat Procession to firmly protect cultural art and prevent cultural deterioration.